Analysis of scientific production on organizational innovation - Néstor Montalván-Burbano; Miguel Pérez-Valls; José Plaza-Úbeda (Cogent Business & Management, 2020)
Studies in organizational innovation have shown rapid growth in the last two decades, so it is necessary to perform a qualitative and quantitative analysis of scientific production to know its current status and development in business activity. In this research, bibliometric analysis and mapping were performed on the publications indexed in the Scopus database between 1996 and 2015, obtaining relevant information on scientific production, contributions by region/country, institutions involved, topics and influential authors. A map of terms was generated that establishes research areas related to organizational systems, firm relations and organizational change, as well as a map of citations showing the disciplines of administration, dynamic capacities and organizational learning related to the subject of study and its main exponents. The findings of the study allow identifying areas of current interest and research potential in Organizational Innovation.
Keywords: 650; bibliometrics; bibliometric mapping; scientific production; organizational innovation; management innovation